Food Redistribution in the Nordic Region - Gram-Hanssen, Irmelin (TemaNord, 2016)
The Nordic Food Redistribution Project investigates food waste reduction through the redistribution of surplus food. The project goal is to increase and improve redistribution activities from donors to food banks and charity organisations in order to enhance both environmental and social sustainability in the Nordic region. The phase II report proposes best practice models concerning legislation, organisation, quality assurance and registration of food. Report recommendations are addressed at redistribution and food-serving actors, donors and authorities and focus on how to improve the quality of redistributed food, how to enhance collaboration between the various actors as well as how to prioritize and secure funding for redistribution activities. The report is part of the Nordic Prime Ministers' green growth initiative: "The Nordic Region - leading in green growth."